Integrated finite strip analysis for long-span cable-stayed bridges. (1st October 2015) - Naderian, Hamidreza; Cheung, Moe M.S.; Shen, Zhenyuan; Dragomirescu, Elena
Highlights: An integrated finite strip discretization is proposed for long-span cable-stayed bridges. The entire bridge can be modeled using the integrated finite strip method. The interactions between different components can be considered in the analysis. The advantages of the method are simplicity of input data and high efficiency. The method is used for static and free vibration analyses of Kap Shui Mun Bridge. Abstract: An integrated finite strip discretization scheme is proposed for modeling long-span cable-stayed bridges. So-called column strips and cable strips model the towers and cables respectively. Also, the structural interactions between different components can be considered in the analysis by defining so-called transition sections. The static and free vibration analyses are performed for Kap Shui Mun Bridge by the integrated finite strip method. The numerical results are verified against other methods. The proposed solution proves to be very efficient in yielding accurate results, in a minimum amount of time while the convergence of the method is still very high.